**Answer:**

Hi there!

Your answer is:

4n^3 -n^2 +4

**Step-by-step explanation:**

(5n^3 +2n^2 +2 ) - (n^3 +3n^2 -2)

First, distribute the negative to the second parentheses!

5n^3 +2n^2 +2 -n^3 -3n^2 +2

Next, combine like terms!

4n^3 -n^2 +4

**Please**** ****let ****me**** ****know**** ****if**** ****you ****have**** ****que****stions****!**

**Answer:**

option C is the correct answer.

**Step-by-step explanation:**

2(m+3)<-5+3m

2m +6 < -5 +3m

2m -3m <-5 -6

-m<-11

m>11

**Answer:**

y = 4x - 3

**Step-by-step explanation:**

Slope = 4

y-intercept = -3

**Answer:**

A

**Step-by-step explanation:**

x^4=64

x^2= +- 8

x = +-sqrt2, x= +- i sqrt2

**Answer:**

The answer to this question may be 2